2004
DOI: 10.1016/s1474-4422(04)00851-8
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for stroke rehabilitation

Abstract: Rehabilitation after hemiplegic stroke has typically relied on the training of patients in compensatory strategies. The translation of neuroscientific research into care has led to new approaches and renewed promise for better outcomes. Improved motor control can progress with task-specific training incorporating increased use of proximal and distal movements during intensive practice of real-world activities. Functional gains are incorrectly said to plateau by 3-6 months. Many patients retain latent sensorimo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
385
0
20

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 606 publications
(409 citation statements)
references
References 139 publications
4
385
0
20
Order By: Relevance
“…As many as 75 % of cases lead to lasting impairments in upper limb function [52]. Physical rehabilitation is the most common post-troke intervention.…”
Section: Preclinical and Clinical Studies For Ischemic Strokementioning
confidence: 99%
See 1 more Smart Citation
“…As many as 75 % of cases lead to lasting impairments in upper limb function [52]. Physical rehabilitation is the most common post-troke intervention.…”
Section: Preclinical and Clinical Studies For Ischemic Strokementioning
confidence: 99%
“…Physical rehabilitation is the most common post-troke intervention. Rehabilitation can yield some functional gains, but recovery is often incomplete and the majority of patients are left with chronic disability [52][53][54]. Motor networks in surviving peri-infarct regions, as well as the undamaged contralateral homotopic cortex and subcortical structures, demonstrate significant reorganization after stroke [55][56][57].…”
Section: Preclinical and Clinical Studies For Ischemic Strokementioning
confidence: 99%
“…In such cases, robotic devices could be coupled to techniques aimed at reducing muscular tone (e.g. pharmaceutical drugs or functional electrical stimulation) for the sake of performing continuous motions and limiting the occurrence of limbs contractures due to excessive immobilization [5]. Other important issues to be considered for unsupervised use in ADL are also related to safety and acceptance [3].…”
Section: Discussionmentioning
confidence: 99%
“…According to the feedback we collected and based on previous literature research [4], [5], [17], the tasks identified as fundamental for regaining independence in ADL were: eating, drinking, toileting and using devices for communication (such as smartphones and computers). Many of these tasks can be performed through the combination of a restricted set of hand motions: power grasp (using all fingers, e.g.…”
Section: ) Design Requirementsmentioning
confidence: 99%
See 1 more Smart Citation